Analisis Manajemen Risiko Dalam Pengambilan Keputusan Brand Owner Entertaiment di Mimi Live House - Muhammad Nasyubun; M Agung Akhdani (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
The F&B business remains a promising industry to pursue due to its large market potential. Especially in Indonesia, with a population of 281.6 million people, it represents an attractive target market for the F&B industry. One of the strategies that companies in the lifestyle and F&B industry can implement is to offer live music, events, and other forms of entertainment to attract the public and encourage customer loyalty to the industry.This study aims to analyze risk management in decision-making by the entertainment brand owner at MIMI LIVEHOUSE. The research uses a qualitative approach and using interviews as the primary method applying risk management analysis stages, which include risk identification, risk analysis, risk evaluation, risk assessment, and risk control.The findings of this study show that risk identification is carried out before the performers go on stage in order to detect any issues that might disrupt the performance. Risk analysis is conducted through rehearsals to minimize errors during performances. Risk evaluation is done by holding daily briefings with the talent and more comprehensive evaluations every three months. Risk assessment is carried out for each performance, with assessment indicators such as stage presence, Mandarin pronunciation, and overall performance commitment. Risk control by the entertainment brand owner is achieved by continuously innovating and developing the Mandarin-style concept.